2001
DOI: 10.1007/s004280000392
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α and C-ERBB-4 expression in breast carcinomas

Abstract: The presence of estrogen receptors (ERs) in breast carcinomas is important for clinical response to endocrine therapy. However, the cellular mechanisms following ER activation are not fully understood. It has been indicated that expression of the ER is associated with the expression of c-erbB-4. To address this question, 103 breast carcinoma samples were studied using reverse transcriptase polymerase chain reaction (RT-PCR) analysis after application of a microselection method for RNA isolation. Total RNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…The WWP1 protein expression has been associated with positive ER-a and good-prognosis breast tumors (Nguyen Huu et al, 2008;Chen et al, 2009). Consistently, most publications associated the ErbB4 protein expression with ER-a-positive, low grade and more differentiated breast tumors (Tang et al, 1999;Suo et al, 2001;Witton et al, 2003;Junttila et al, 2005). However, knockdown of endogenous WWP1 significantly upregulates endogenous ErbB4 protein expression in both T47D and MCF7 (Figure 4a).…”
Section: Discussionsupporting
confidence: 57%
“…The WWP1 protein expression has been associated with positive ER-a and good-prognosis breast tumors (Nguyen Huu et al, 2008;Chen et al, 2009). Consistently, most publications associated the ErbB4 protein expression with ER-a-positive, low grade and more differentiated breast tumors (Tang et al, 1999;Suo et al, 2001;Witton et al, 2003;Junttila et al, 2005). However, knockdown of endogenous WWP1 significantly upregulates endogenous ErbB4 protein expression in both T47D and MCF7 (Figure 4a).…”
Section: Discussionsupporting
confidence: 57%
“…Most studies presented to date do not have congruent findings regarding the prognostic effect of c-erbB-4 in breast cancer. Some studies linked c-erbB4 overexpression with a well-differentiated phenotype (Kew et al, 2000;Suo et al, 2002), positive ER status (Knowlden et al, 1998;Suo et al, 2001) and longer survival (Suo et al, 2002;Witton et al, 2003). Another study associated overexpression with poor survival in lymph node-positive cases (Lodge et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations have been found between c-erbB-3 overexpression and tumour size (Travis et al, 1996) and histological grade (Naidu et al, 1998). Studies on c-erbB-4 expression have shown an association with well-differentiated tumours (Kew et al, 2000;Suo et al, 2002) and positive ER status (Suo et al, 2001). Some studies have found an association with better survival (Pawlowski et al, 2000;Suo et al, 2002), while others have reported an association with poor survival (Lodge et al, 2003) or no association with survival (Kew et al, 2000).…”
mentioning
confidence: 99%
“…Thus the role of nuclear 4ICD shifts from a benign STAT5A coactivator driving differentiation in the normal breast to an ERα coactivator promoting breast tumor proliferation. There is a strong selection for the ERα/4ICD signaling axis in developing tumors with several studies reporting between 74-91% of low grade ERα(+) tumors coexpressing HER4 [43,45,61]. Clinically this combination of ERα expression and nuclear accumulation of the 4ICD/ERα transcriptional complex predicts worse patient prognosis than the combination of ERα and membrane associated HER4 [20,28] providing strong clinical support for a ERα/4ICD tumor cell proliferation signal.…”
mentioning
confidence: 99%